Deformities in reared cobia, Rachycentron canadum L. and grouper, Epinephelus marginatus, in São Paulo state coast, Brazil: case report - J.R. Engrácia Filho; M.T. Shimada; J. Yunis-Aguinaga; F.C. Ramos-Espinoza; F.R. Moraes; J.R.E. Moraes (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT Skeletal deformities are frequent problems in cultured fish populations due mainly to unfavorable abiotic conditions, inappropriate nutrition, and genetic factors. These may cause erratic swimming, decrease of conversion rate, growth, and market value. The aim of this case report was to present the occurrence of deformities in juvenile cobia and groupers from an offshore marine farm in Ilhabela, São Paulo, Brazil. Nine cobias and seven juvenile groupers, that presented deformities, were euthanized and fixed in 10% formaldehyde. They were tagged, processed, and stained with "Alcian Blue" (AB) and "Alizarin Red-S" (ARS) for visualization of cartilage and bone tissue, respectively. After evisceration, radiographic examination was performed. The deformities observed in cobia were atrophy of the operculum, disorganization of the gill lamellae, deformity of the lower jaw, kyphosis, and scoliosis. Groupers presented lower jaw deformity and saddleback syndrome. The farm studied in this case report had poor management standards, fed commercial feed for freshwater herbivorous fish and cooked sardines, high inbreeding and absence of adequately trained professionals to manage these species. The sum of these factors must have directly influenced the appearance of these deformities. It is necessary to control this situation to minimize the incidence of malformations that have economic impacts to farmers.